Relevansi dan Interpretatif Laporan Keuangan Berdasarkan Metode General Price Level Accounting - David Sukardi Kodrat (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
The recent economic matters of Indonesia is sign of inflation. Inflation is a rise in the general level prices over time of a specific set of goods and services. In Indonesia, inflation rate is reported based on Consumer Price Index until 2007 always more than 5 percent unless in 1985 as 4.3 percent. The latest five year from 2003 to 2007 are 6.8%, 6.06%, 10.4%, 14,8% and 6.4%. It showed that a rise in the prices of a goods and services are influenced directly to change of purchasing power and production cost or the factors of production. Although the inflation is under two digits, inflation only above five percent is too high if its compare to gross national product. Generally, Financial Statements are arranged based on Historical Cost Accounting (HCA). By using this method, financial statements are arranged by using the price of transaction arise. As tool of measure or exchange in economy is used a monetary unit. Inflation is caused a monetary unit to be not stable. Financial statement is arranged based on Historical Cost Accounting not reflecting a change of purchasing power. Financial statement that reflect a change of purchasing power is General Price Level Accounting. This research uses case and field study by using purposive sampling. Analysis are using the number of dollar (NOD) attribute and the command over good (COG) attribute. NOD attribute is used to test that financial statements are interpretative and COG attribute is used to test that financial statements are relevance. The result of NOD attribute shows from 27 item, there are 92,59 percent is interpretative and the result of COG attribute, there are 74,07 percent is relevance. It means that financial statement is arranged by using General Price Level Accounting more interpretative and relevance than financial statement that arranged by using Historical Cost Accounting.